2020
DOI: 10.1002/brb3.1529
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing radiation modulates vascular endothelial growth factor expression through STAT3 signaling pathway in rat neonatal primary astrocyte cultures

Abstract: Background and Purpose: Radiation-induced brain injury (RBI) usually occurs six months to three years after irradiation, often shows cognitive dysfunction, epilepsy, and other neurological dysfunction. In severe cases, it can cause a wide range of cerebral edema, even herniation. It seriously threatens the survival of patients and their quality of life, and it becomes a key factor in limiting the radiation dose and lowering the therapeutic efficacy in recent years. Therefore, studying the pathogenesis of RBI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“… 37 Knowing that NF-κB upregulates pro-inflammatory cytokines production, including that of IL-1β and TNF-α, which in turn increases BBB permeability and evolves demyelination and edema. 38 Previously, it was reported that TNF-α played a critical role in radiation-induced vascular damage, BBB disruption and astrogliosis, where the binding of TNF-α to its receptors on the endothelial cell surface activates NF-κB, which in turn upregulates the synthesis of intercellular adhesion molecule-1 causing increases leukocyte-endothelial cell interactions. Consequently, it increases infiltration of immune and inflammatory cells through the damaged BBB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 37 Knowing that NF-κB upregulates pro-inflammatory cytokines production, including that of IL-1β and TNF-α, which in turn increases BBB permeability and evolves demyelination and edema. 38 Previously, it was reported that TNF-α played a critical role in radiation-induced vascular damage, BBB disruption and astrogliosis, where the binding of TNF-α to its receptors on the endothelial cell surface activates NF-κB, which in turn upregulates the synthesis of intercellular adhesion molecule-1 causing increases leukocyte-endothelial cell interactions. Consequently, it increases infiltration of immune and inflammatory cells through the damaged BBB.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed a positive correlation between the VEGF expression and the brain injury in mice exposed to 20 Gy whole-brain irradiation. 2 Besides, in vitro study has demonstrated that VEGF expression in astrocytes increased significantly in a dose-dependent manner (Zhou et al 2020). 39 However, VEGF inhibition may have a potential for treatment of brain injury in irradiated and ischemic experimental animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group described that JAK2 is overexpressed in a BLM-induced fibrosis rat [20,21] IL-13 → JAK1/TYK2 → STAT6 AECs from BLM-induced fibrosis mouse model [20,21] IL-6 → STAT3 IPF fibroblasts, normal lung fibroblasts and BLM-induced mouse model [22][23][24] IL-11 → STAT3 BLM-induced fibrosis mouse model, human lung fibroblasts [25][26][27] IL-31 → STAT1 Mouse pulmonary fibrosis [28] TGF-β1 → STAT3 Human fibroblasts, AECs, SS mouse model [29,30] TGF-β1 → JAK2 → STAT3 IPF AECs and fibroblasts, SS [31,32] EGF → STAT3 IPF, COP, NSIP [33,34] PDGF → STAT1 ILDs alveolar macrophages, IPF BALF [35][36][37] FGF → STAT1/STAT3/STAT5 Progressive fibrosing ILD [38,39] VEGF → STAT3 IPF, Idiopathic interstitial pneumonia [40,41] Abbreviations: alveolar epithelial cells (AECs), bleomycin (BLM), systemic sclerosis (SS), idiopathic pulmonary fibrosis (IPF), cryptogenic organizing pneumonia (COP), idiopathic nonspecific interstitial pneumonia (NSIP), bronchoalveolar lavage fluid (BALF).…”
Section: Jak/stat Lung Expression and Distributionmentioning
confidence: 99%
“…Recent evidence shows that VEGF constitutes an exhaled biomarker in IPF, with significant correlations with the clinical manifestations [55], and patients with idiopathic interstitial pneumonia have higher VEGF levels in plasma [56]. VEGF is associated with STAT3 in primary astrocytes when ionizing radiation-induced overexpression of VEGF leads to STAT3 activation [40]. Moreover, STAT3 has a binding site on the VEGF promoter and can regulate VEGF expression [41].…”
Section: Activation By Growth Factorsmentioning
confidence: 99%